(3GdLeY Hjf QLGd GdUMjMjfs - (3GHf GdbjSQGfj , eMeO Hf WGgQ Hf eMeO GdebOSj, CHh GdaVd,J (B507 (3g` s ((3eMehO Hf fGUQ Hf YHjO Gddg GdYLei s)
(3ChdgG (B:s
(3GdMeO ddg Ydi cd MGd hCeGe cd MGLI s
(3BNQgG (B:s
(3jYfi MOjKg Yf GdHQGA (B:(3Ef Chd eGfHJOF Hg jhefG Cf fUdi Ke fQLY affMQ GdMOjK s
(3LeY GdeDda ajg cJGHi CHj fUQ GdcdGHGPis
(3hCHi HcQ GdCUagGfis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3LeY s
Keywords: (3GdJGQjNs